Irony, Ethics, and Humanism: The Politics of Irony and Moral Resistance in Coetzee’s Age of Iron - Sapkota, Tika Ram (Journal of Interdisciplinary Studies, 2025)
This study examines the politics of irony and moral resistance in J. M. Coetzee’s Age of Iron focusing on role of irony in both a narrative and ethical strategy to critique apartheid South Africa. Through textual and thematic analysis, supported by the theories of irony, ethics and humanism the research particularly explores how Coetzee employs irony to expose racial violence, moral complicity, and the possibility of human transformation. The novel’s protagonist, Mrs. Elizabeth Curren, embodies Coetzee’s moral vision as she confronts her own complicity and gradually develops empathy toward the marginalized black population. Based on the notions of the “said and unsaid” this paper illuminates how irony destabilizes dominant discourse, while humanism and ethics of responsibility underscore the novel’s call for moral awakening through recognition of the other. The analysis reveals that Coetzee’s irony bridges the divide between fiction and history, transforming personal suffering into a collective ethical inquiry. Ultimately, Age of Iron stands as a moral allegory of guilt, empathy, and redemption, demonstrating that literature can act as a historical intervention, one that exposes injustice, challenges indifference, and reaffirms shared humanity in the face of oppression.